Advances in Transportation Geotechnics IV Proceedings of the 4th International Conference on Transportation Geotechnics Volume 2 - Tutumluer, Erol.; Nazarian, Soheil; Al-Qadi, Imad.; Qamhia, Issam I.A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This volume presents selected papers presented during the 4th International Conference on Transportation Geotechnics (ICTG). The papers address the geotechnical challenges in design, construction, maintenance, monitoring, and upgrading of roads, railways, airfields, and harbor facilities and other ground transportation infrastructure with the goal of providing safe, economic, environmental, reliable and sustainable infrastructures. This volume will be of interest to postgraduate students, academics, researchers, and consultants working in the field of civil and transport infrastructure. .
Keywords: Engineering geology; Geotechnical engineering; Transportation engineering; Traffic engineering; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Transportation Technology and Traffic Engineering; Engineering geology -- Congresses; Transportation engineering -- Congresses